The Demographic Theory and International Conflicts: An Analytical Approach - benkacir, MOUSSA Benkacir (The International and Political Journal, 2025)
This article addresses the problem of the relationship between demographic factors and international conflicts, aiming to explore its importance in the strength of states and the reliance of various societies on it to engage in wars even if their nature changes. The size of the population, age structure, and the cohesion of the population play a role in the decision to enter into a conflict, whether international or internal. As a result, we find that the demographic factor has a clear impact on the trajectories of conflicts, transitioning from a latent to a manifest state. Conflicts, in turn, negatively affect the demographic factor, leading to issues such as displacement, a decrease in population numbers, and disruption in natural population growth rates, consequently affecting the overall stability of the state